MINAT REMAJA UNTUK MELANJUTKAN PENDIDIKAN KE JENJANG YANG EBIH TINGGI DI KELURAHAN TELUK KABUNG UTARA BUNGUS TELUK KABUNG PADANG - Romadani, Robi; Arief, Asmaiwaty; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
The study in based on the phenomenon that is still found in the area of youth Teluk Kabung Utara Bungus Teluk Kabung Padang, has not indicated an interest to continue their education to higher level. Therefore researches interested in studying about interest teens to continue their education to a higher level in the village Teluk Kabung Utara Bungus Teluk Kabung Padang. The research is a descriptive study. Population in this study is that adolescents are in the village Teluk Kabung Utara. That were limited to junior high level which amounts to 32 people. Sampling method in this study by using total sampling technique, ie all the population sapled. Data collection techniques in this study using a questionnare given to adolescents sapled. The results of the data in this study were processed using techniques percentage. Based on results of various indicators in the said. The general interest in youth to continue their education on the criteria being the percentage of 43.75%, so it can be concluded adolescent interest in education is still low. Advice for teen writers, still eager to continue their education, because education is useful for a better future.